2021
DOI: 10.25165/j.ijabe.20211405.6258
|View full text |Cite
|
Sign up to set email alerts
|

Rapid estimation of apple phenotypic parameters based on 3D reconstruction

Abstract: In order to obtain the phenotypic parameters of apple quickly and accurately, which were commonly used as the basis of fruit sorting, a fast estimation method of apple phenotypic parameters based on three-dimensional (3D) reconstruction was proposed in this study. In this study, a three-dimensional model was constructed to estimate the phenotypic parameters of apple, such as volume, height, diameter, and fruit shape index. Firstly, an image acquisition system was built to capture sequence images of fruit with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In recent years, the use of machine vision to predict the weight of agricultural products has been frequently reported [4][5][6][7][8]. The research methods used in these studies and their advantages and disadvantages are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of machine vision to predict the weight of agricultural products has been frequently reported [4][5][6][7][8]. The research methods used in these studies and their advantages and disadvantages are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%